Comparing Postoperative Sore Throat (POST) following intubation using Macintosh Laryngoscope Versus C-MAC® Video Laryngoscope - Khoo, B.H.; Yeoh, Chih Nie; Lee, Choon Yee; Nadia Md Nor,; Raha Abd Rahman, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Postoperative sore throat (POST) is a common complication with incidence of 30-90% when intubation was done using conventional Macintosh laryngoscope. Although POST is usually self-limiting and with no long-term morbidity, it can lead to patient’s discomfort and dissatisfaction in the postoperative period. The objective of this study was to compare the incidence of POST following intubation using Macintosh laryngoscope and C-MAC® videolaryngoscope (VL) at various time intervals post anaesthesia. This prospective randomised controlled study comprised of 128 patients with American Society of Anesthesiologists (ASA) I and II status who underwent elective surgery under general anaesthesia in Universiti Kebangsaan Malaysia Medical Centre. All recruited patients have normal airway and divided randomly into Group 1 and Group 2 that used Macintosh laryngoscope and C-MAC® VL during intubation, respectively. Patients were evaluated for sore throat, hoarseness of voice, dysphagia and coughing at recovery, 6 hours, 12 hours and 24 hours after intubation. Severity of POST was assessed using numerical rating scale (NRS). Incidence of POST was found to be higher in the Macintosh laryngoscope group (61.9%) compared to C-MAC® VL group (47.9%) although the difference was not statistically significant (p=0.107). Median pain score was used to assess the severity of POST, showing low and comparable in both groups at all time intervals. There were also no significant differences seen in hoarseness of voice, coughing and dysphagia for both groups during postoperation. Incidence of POST following intubation using C-MAC® VL and conventional Macintosh laryngoscope were comparable. This study revealed that severity of POST was generally low in both groups.